2020
DOI: 10.1111/1753-0407.13113
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of gestational diabetes mellitus heterogeneity and prepregnancy body mass index to large‐for‐gestational‐age infants—A retrospective case‐control study

Abstract: Objective To study the associations between heterogeneity of gestational diabetes mellitus (GDM) subtype/prepregnancy body mass index (pre‐BMI) and large‐for‐gestational‐age (LGA) infants of Chinese women. Methods We performed a retrospective case‐control study of 299 women with GDM and 204 women with normal glucose tolerance (NGT), using oral glucose tolerance test‐based indices performed at 24‐25 weeks of gestation. Women with GDM were classified into the following three physiologic subtypes: GDM with a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…The heterogeneity of physiologic hyperglycemia among women with GDM may explain this inconsistency from a new perspective. Our previous research found that GDM women of the three subtypes had different clinical characteristics, 10 and we speculate that the discrepancy of risk factors also existed among the three GDM subtypes.…”
Section: Introductionmentioning
confidence: 72%
“…The heterogeneity of physiologic hyperglycemia among women with GDM may explain this inconsistency from a new perspective. Our previous research found that GDM women of the three subtypes had different clinical characteristics, 10 and we speculate that the discrepancy of risk factors also existed among the three GDM subtypes.…”
Section: Introductionmentioning
confidence: 72%
“…There is currently considerable interest in elucidating the heterogeneity of diabetes, with the recognition that such understanding may enable precision medicine, as recently highlighted in a consensus report from the American Diabetes Association and the European Association for the Study of Diabetes [21]. In this context, the initial report of GDM heterogeneity by Powe et al [4] has led to a series of recent studies evaluating GDM subtypes in relation to pregnancy outcomes [5][6][7][8]. These observational studies have been fairly comparable in the maternal phenotypes identified by their subtypes but less consistent in their obstetrical/neonatal findings [4][5][6][7][8], likely reflecting the confounding effect of the clinical management of GDM on the latter associations and some differences between studies in the diagnostic criteria by which defects in insulin sensitivity and insulin secretion were defined.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the initial report of GDM heterogeneity by Powe et al [4] has led to a series of recent studies evaluating GDM subtypes in relation to pregnancy outcomes [5][6][7][8]. These observational studies have been fairly comparable in the maternal phenotypes identified by their subtypes but less consistent in their obstetrical/neonatal findings [4][5][6][7][8], likely reflecting the confounding effect of the clinical management of GDM on the latter associations and some differences between studies in the diagnostic criteria by which defects in insulin sensitivity and insulin secretion were defined. In the current study, the subtypes were defined in precisely the same manner as in the initial report by Powe et al .9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, multiple previous studies found women with GDM had higher BMI than women free of GDM [30,31,32] detected reduced risk of GDM with their proposed diet and exercise interventions for pregnant women versus women received no intervention. Recently, Qiu et al, [33] reported that for pre-pregnancy BMI, significant differences were found in GDM incidence between the different groups according to BMI and Wang et al, [34] found women with GDM with a predominant insulin-sensitivity defect had a higher pre-BMI. These findings could be attributed to the fact that plasma concentrations of adipokines, which may contribute directly and/or indirectly for glucose intolerance, are influenced by the amount of adipose tissue present before and/or during the pregnancy [35] .…”
Section: Discussionmentioning
confidence: 99%